Architectural production of the centenary of Algeria 1930 between tradition and modernism - Benarbia, Hala; Belabed Sahraoui, Badia (Humanities, Arts and Social Sciences Studies, 2024)
In 1930, France commemorated the centenary of its occupation of Algeria, marking a significant historical event. On this occasion, prominent public edifices were erected, mainly in the departmental capitals: Algiers, Oran, and Constantine. These structures were accompanied by notable urban enhancements. The aim of this article is to explore the distinctive attributes of these constructions, emphasising the architectural and aesthetic idioms used in their creation. The methodology employed in this study involves a comprehensive examination of archival materials sourced from France and Algeria, as well as the digital library BNF Gallica. By delving into these resources, we aim to uncover the underlying reasons and influences that guided the design and execution of these architectural ventures. The public buildings erected during this period indicate the colonial power's deliberate political agenda, serving as a testament to their strategy of showcasing a modernized Algeria during the centenary celebration. Our analysis sheds light on the intricate interplay between classical and contemporary architectural influences that shaped the Algerian architectural landscape during the centenary celebration. By scrutinising the foremost architectural accomplishments, we can discern how architects and policies converged to define the architectural ethos of this transformative era. A major aspect that emerges from our research is the fusion of traditional design elements with a simplified and streamlined aesthetic, exemplifying the core essence of these structures. The amalgamation of stylised traditional forms with the elegance of minimalist lines and shapes epitomises the principal characteristics of this architectural production.